1998
DOI: 10.2134/jeq1998.00472425002700010029x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Organic Carbon and Carbon Dioxide Fluxes in Maize Fields Receiving Spring‐Applied Manure

Abstract: More than 19 million Mg of dairy manure are produced annually in the Canadian provinces of Quebec and Ontario, and most of it is spread on agricultural fields. Quantitative information on the impact of manure management practices on levels of soluble organic carbon (SOC) and emissions of CO2 is important for assessing whether this management significantly contributes to increasing atmospheric CO2 concentrations. The objective of this study was to measure the effects of dairy cattle manure (applied at 0, 56, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 0 publications
0
33
2
Order By: Relevance
“…For example, small (Rochette et al 2000) and large increases in K 2 SO 4 -extractable organic C were reported in a loamy soil receiving liquid hog manure. Similarly, manureinduced increases in soil WEOC content are much smaller in the present study than those observed by Gregorich et al (1998) and Rochette and Gregorich (1998) in a loamy soil receiving solid dairy cattle manure. Greater soil C extraction efficiency with 0.5 M K 2 SO 4 solution (Gregorich et al 1998; Rochette and Gregorich 1998), compared with the 5 mM CaCl 2 used in the present study, may partly explain the difference (Zsolnay 1996;Chantigny 2003).…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…For example, small (Rochette et al 2000) and large increases in K 2 SO 4 -extractable organic C were reported in a loamy soil receiving liquid hog manure. Similarly, manureinduced increases in soil WEOC content are much smaller in the present study than those observed by Gregorich et al (1998) and Rochette and Gregorich (1998) in a loamy soil receiving solid dairy cattle manure. Greater soil C extraction efficiency with 0.5 M K 2 SO 4 solution (Gregorich et al 1998; Rochette and Gregorich 1998), compared with the 5 mM CaCl 2 used in the present study, may partly explain the difference (Zsolnay 1996;Chantigny 2003).…”
Section: Discussioncontrasting
confidence: 62%
“…On average for the 2 yr, soil WEOC content was 6.7 mg kg -1 greater with liquid manure and 7.2 mg kg -1 greater with solid manure than with the control; differences between the two manures were not statistically significant. Many others have reported an immediate increase in soil C extractable with aqueous solutions following amendment with animal manure (Kirchmann and Lundvall 1993;Gregorich et al 1998;Rochette and Gregorich 1998;Rochette et al 2000Rochette et al , 2004; however, the magnitude of the response among studies was variable. For example, small (Rochette et al 2000) and large increases in K 2 SO 4 -extractable organic C were reported in a loamy soil receiving liquid hog manure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Red clover has been found to increase yields in the subsequent year by improving soil structure and microbial activity, by accelerating the decomposition of wheat straw (Drury et al 1999), by providing organic N through N 2 fixation (Bruulsema and Christie 1987), and by adding a large amount of organic C to the soil. Addition of organic compounds and fertilization has been shown to increase the content of SDOC by a factor of 2.7 to 3.2 Gregorich et al 1998). In manured soils, soluble C increased dramatically after manure application, followed by a gradual decrease over time .…”
mentioning
confidence: 99%